Consistency of PPP GPS and strong-motion records: case study of Mw9.0 Tohoku-Oki 2011 earthquake - Psimoulis, Panos; Houlié, Nicolas; Meindl, Michael; Rothacher, Markus (Techno-Press, 2015)
GPS and strong-motion sensors are broadly used for the monitoring of structural health and Earth surface motions, focusing on response of structures, earthquake characterization and rupture modeling. Several studies have shown the consistency of the two data sets within at certain frequency (e.g., 0.03<f<0.2Hz). The compatibility of Precise Point Positioning (PPP) GPS and strong-motion data was assessed by comparing their respective displacement waveforms for several frequency bands (f<0.3Hz). For this purpose, there are used GPS and strong-motion records of the Mw9.0 Tohoku 2011 earthquake at 23 very close spaced sites and conclude that the agreement between the two datasets depends on the frequency of the excitation, the direction of the excitation signal and the distance from the excitation source.